Economics : an A-Z guide - Bishop, Matthew (London : Profile books, 2009)
This book is a clear and lively guide to the essentials of economics, with entries that stretch from A to Z and cover such topics, terms and jargon as: Animal spirits, Barter, Cannibalise, Dumping, Economic man, First-mover advantage, Gresham's Law, Hypothecation, Inequality, J-curve, Kleptocracy, Lump of labour fallacy, Money illusion, New economy, Opportunity cost, Positional goods, Queueing, Random walk, Satisficing, Tragedy of the commons, Utility, Value at risk, Winner-takes-all markets, X-efficiency, Yield gap and Zero-sum game.
At head of title: The economist.
nif 17/05/13; nmn 13/06/13
Ref.
Keywords: Economics; Economics